First faunal record of larval and juvenile gobies (Actinopterygii: Gobiiformes) in the Ka Long estuary, northern Vietnam - Thuy, Ta Thi; My, Nguyen Ha; Hau, Tran Duc (Academia Journal of Biology, 2022)
Gobies are dominant in terms of both species diversity and abundance in estuarine habitats, but little is known about their early developmental stages in the coastal waters of Vietnam. To examine species diversity of goby larvae and juveniles, monthly collections were carried out using a small seine net from the Ka Long estuary in the northernmost Vietnamese coast, from September 2014 to August 2015. A total of 1,334 goby fishes of 20 species or more in three families (Butidae, Oxudercidae and Gobiidae) were caught, including nine unidentified species. This is the first record of gobies at early developmental stages from an estuary in Vietnam. The family Oxudercidae was the most abundant in terms of total species, and Gobiopterus chuno was the most frequent species in the study area. The goby specimens collected were mostly postflexion larvae and juveniles, ranging from 2.3 mm to 99.1 mm in body length. The size of nine dominant gobies was around 10 mm body length. In the study site, goby fishes are from tropical, subtropical and temperate zones, suggesting this goby fauna can display transitional biodiversity from tropical to temperate waters.